Pemanfaatan Perpustakaan Dengan Hasil Belajar Pada Mata Kuliah Higiene Dan Sanitasi PKK Fakultas Teknik - riwayati, riwayati; baidar, baidar; syarif, wirnelis (Journal of Home Economics and Tourism, 2013)
ABSTRACTThis study aimed to determine the relationship of the use of libraries UNP with learning outcomes at the course hygiene and sanitation courses PKKFakulty Technical State University in Padang. The research method used isdescriptive quantitative type of ex-post facto correlational approach. Thesampling technique used in this study is random sampling with a sample of 70people. The results showed that Fhitung is 27.69, while the F table = 3.99.Fhitung> F table, it can be concluded that the relationship between thevariables X and Y is linear. The results of statistical tests show that there is apositive and significant correlation of 0538, the results of the significance testof correlation coefficient Sig (p) obtained was 0000. where 0.000 <0.05, thenHo is rejected. To the conclusion that there is a positive and significantrelationship between the use of the library to the value of subjects of hygieneand sanitation in the family welfare program student study culinaryconcentration PKK. Keywords: Utilization Library, Learning Outcomes, Value Hygiene AndSanitation,Â